A Novel Fc-Engineered Anti-HER2 Bispecific Antibody With Enhanced Antitumor Activity. Issue 4 (20th May 2023) - Mohammadi, Mehdi; Jeddi-Tehrani, Mahmood; Golsaz-Shirazi, Forough; Arjmand, Mohammad; Torkashvand, Fatemeh; Bahadori, Tannaz; Judaki, Mohammad Ali; Shiravi, Fariba; Ahmadi Zare, Hengameh; Notash Haghighat, Farzaneh; Mobini, Maryam; Shokri, Fazel; et al.
Abstract : Human epidermal growth factor receptor 2 (HER2) overexpression has been demonstrated in a variety of cancers. Targeted therapy with anti-HER2 monoclonal antibodies (mAbs) has been approved as a therapeutic modality. Despite the efficacy of mAbs in tumor treatment, many patients do not benefit from this therapeutic platform. Fragment crystallizable (Fc) engineering is a common approach to improve the efficacy of therapeutic mAbs. Five Fc-engineered mAbs have so far been approved by FDA. We have recently developed an anti-HER2 bispecific mAb, BiHT, constructed from variable domains of trastuzumab, and our novel humanized anti-HER2 mAb, hersintuzumab. BiHT displayed promising antitumor activity as potently as the combination of the parental mAbs. Here, we aimed to modify the Fc of BiHT to improve its therapeutic efficacy. The Fc-engineered BiHT (MBiHT) bound to recombinant HER2 and its subdomains with an affinity similar to BiHT. It also recognized native HER2 on different cell lines, inhibited their proliferation, downregulated HER2 expression, and suppressed downstream signaling pathways similar to BiHT. Compared with BiHT, MBiHT displayed enhanced antibody-dependent cellular cytotoxicity activity against various tumor cell lines. It also inhibited the growth of ovarian xenograft tumors in nude mice more potently than BiHT. Our findings suggest that MBiHT could be a potent therapeutic candidate for the treatment of HER2-overexpressing cancer types.